Reaching the Unreached: Bridging Islam and Science to Treat the Mental Wounds of War - Zoellner, Lori A.; Bentley, Jacob A.; Feeny, Norah C.; Klein, Alexandra B.; Dolezal, Michael L.; Angula, Dega A.; Egeh, Momin H. (Frontiers in Psychiatry, 2021)
Radical new paradigms are needed to equip non-professionals and leverage community faith-based infrastructure to address the individual and communal wounds of war- and conflict-related trauma. Muslims in war-torn regions like Somalia experience high rates of trauma and posttraumatic stress; yet, lack of providers, potential stigma, and lack of integration with one’s faith are substantial barriers to care. In this pre-post feasibility clinical trial (NCT03761732), mosque leaders implemented a brief, group- and mosque-based intervention, Islamic Trauma Healing, targeting trauma-related psychopathology and community reconciliation for trauma survivors (N = 28) in Somaliland, Somalia. Leaders were trained in a brief 2-day training, with supervision provided remotely via WhatsApp. This six-session intervention combines empirically-supported trauma-focused psychotherapy and Islamic principles, focusing on wisdom from the lives of the Prophets and turning to Allah in dua about trauma. There were large, clinically meaningful effects for PTSD (g = 1.91), depression (g = 2.00), somatic symptoms (g = 2.73), and well-being (g = 1.77). Qualitative data from group members highlighted how well the program was aligned with their Islamic faith, built community, and need to expand the program. These results highlight the feasibility of this non-expert, easily up-scalable mental health approach in war-torn Muslim regions and refugee communities. This program has the potential to provide a low-cost, self-sustaining, Islam-based intervention addressing the psychological wounds of war consistent with the IOM’s call to develop novel approaches to address unmet clinical needs.